Disadvantaged Childhoods and Humanitarian Intervention
XIII, 232 p. 7 illus., 4 illus. in color.
Keywords: This book explores how humanitarian interventions for children in difficult circumstances engage in affective commodification of disadvantaged childhoods. The chapters consider how transnational charitable industries are created and mobilized around childhood need—highlighting children in situations of war and poverty, and with indeterminate access to health and education—to redirect global resource flows and sentiments in order to address concerns of child suffering. The authors discuss examples from around the world to show how, as much as these processes can help achieve the goals of aid organizations, such practices can also perpetuate the conditions that organizations seek to alleviate and thereby endanger the very children they intend to help.